Revisiting Aloe dichotoma’s suitability as an indictor of climate change in southern Africa - Jack, Samuel Linton (Department of Biological Sciences, 2019)
Apparent recent population contractions at Aloe dichotoma’s equatorward range limit have led this iconic arborescent succulent to be cited as one of the first biological indicators of the impact of anthropogenic climate change in southern Africa. However, prior evidence from historical photography of populations as well as detailed botanical field notes indicated that mortality was already pervasive in the southern and central distribution of the species within the first half of the 20th century. This, as well as possible previous assumptive and interpretive problems prompted a reassessment of the evidence for A. dichotoma’s promotion as a climate change indicator species. In the current study, a framework for assessing species vulnerability to climate change was used to determine A. dichotoma’s exposure, sensitivity, and adaptive capacity to climate change impacts. First I evaluated A. dichotoma’s exposure to climate change by independently assessing historical rainfall and temperature records of the longest possible duration, and specific to A. dichotoma’s distributional extent, in order to evaluate how average conditions and temporal trends might contribute to demographic patterns. I then made use of very high spatial resolution demographic information collected during a roadside mega-transect in order to re-examine the merits of a latitudinal cline in mortality. Subsequently, I related demographic patterns to a detailed contemporary climate surface in order to gauge the strength of the relationship between the two, as well as to determine the relative sensitivity of juvenile and adult life history stages. Additionally, with the aid of detailed population-level sampling and averaged solar radiation values for opposing aspects, I investigated A. dichotoma’s adaptive capacity in terms of its ability to recruit to more favourable aspects. In this respect, a new technique was developed to determine the approximate time since death of in situ skeletons, as well as the age classes from which they were derived. Lastly, study results were interpreted in relation to A. dichotoma’s life history traits to determine the likelihood of a recent response to climate change Despite a paucity in instrumental records and record length, particularly within the equatorward summer rainfall zone (SRZ), encompassing southern and central-western Namibia, historical climate analyses revealed considerable spatial and temporal variability in temperature and, especially, rainfall, within the distribution range of the species. For the SRZ, average climatic conditions were found to be at least as severe within the Gariep River valley, between 28°S and 29°S, as for the equatorward extreme at approximately 21°S, undermining previous inferences of a simple latitudinal climate gradient. Conversely, average rainfall within the poleward winter rainfall zone (WRZ), and south-western extreme of the SRZ, was shown to have been historically higher and more consistent than the SRZ to the north. The natural climatic disjunction between northern and southern rainfall zones has likely had a significant influence on the maintenance of relative latitudinal recruitment and mortality rates in A. dichotoma, and may have contributed to an erroneous attribution of observed mortality to recent, anthropogenic climate change. Historical temperature records indicated an almost uniformly increasing trend throughout the distribution, rising more rapidly within the SRZ. However, rainfall trends were more difficult to interpret, being strongly contingent upon record length, segment of time recorded, and initial and terminal conditions under which the record was established. These interpretive difficulties were considerable for Namibian stations, and advocated a cautious interpretation of negative rainfall trends at several summer rainfall stations, while generally more robust records at winter rainfall stations registered mostly positive trends over the last sixty years. Results from the roadside mega-transect corroborated trends in climatic severity, indicating that proportional mortality had also been greatest within the Gariep River valley between 28°S and 29°S and not at the equatorward range limit as previously suggested. Furthermore, there was only a very weak relationship between age classes and key contemporary climate variables, which suggested an uncoupling between the two. Despite generally poor relationships, juveniles were most responsive to climate and solar radiation gradients, suggesting a greater sensitivity compared to the adult age class, which appeared more resilient. In addition, most mortality was shown not to be recent in origin, but to have occurred several decades ago and to be chiefly derived from larger and, therefore, more climatically-resilient, adult age class rather than smaller, more climatically-sensitive juvenile individuals. In combination with A. dichotoma’s life history traits, including longevity, slow growth and infrequent recruitment, the findings from this study indicate that current demographic patterns reflect longer-term climatic fluctuations rather than recent climate change and that certain climatically marginal populations may be biological relicts of a previously more amenable climate. These findings challenge the view that A. dichotoma has responded negatively to recent, anthropogenically-driven changes in climate and reassert the importance of longer term climatic and demographic processes in shaping patterns currently observed within populations of this species. Coupled with the establishment of a long term ecological research network at key populations spanning the full latitudinal (and longitudinal) range, a greater focus on the regeneration niche and physiological thresholds would help advance our understanding of A. dichotoma’s susceptibility to moisture and temperature deficits arising from climate change. Assessment of the suitability of A. dichotoma as a sentinel of climate change would also be greatly aided by the improved temporal and spatial resolution of historical and palaeo-climatic records within southern Africa. There is an urgent need for this work in the face of possible lagged responses to environmental change within long-lived, infrequently recruiting species, as well as rapidly rising temperatures and uncertainty surrounding future precipitation in the region.